2021
DOI: 10.1016/j.jmig.2020.04.039
|View full text |Cite
|
Sign up to set email alerts
|

Uterus-Sparing Surgery: Outcomes of Transvaginal Uterosacral Ligament Hysteropexy

Abstract: Study Objective: Recently, there has been a paradigm shift toward uterine conservation during the surgical management of pelvic organ prolapse (POP), specifically uterine prolapse. There are few reports on transvaginal uterosacral ligament hysteropexy (TULH). This study aimed to describe our surgical technique and outcomes. Design: Retrospective review and description of surgical technique. Anatomic outcome has been reported using the POP quantification system. Complications were segregated. A comparison of pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 21 publications
2
3
0
Order By: Relevance
“…There are fewer vaginal USHP studies with which to compare our results. Aserlind et al 21 reported a 5% anatomic failure at 17-month follow-up, similar to our rate of 6%. In the largest vaginal USHP retrospective study to date, Romanzi et al 22 reported an 87% anatomic success rate with 24-month follow-up.…”
Section: Discussionsupporting
confidence: 90%
“…There are fewer vaginal USHP studies with which to compare our results. Aserlind et al 21 reported a 5% anatomic failure at 17-month follow-up, similar to our rate of 6%. In the largest vaginal USHP retrospective study to date, Romanzi et al 22 reported an 87% anatomic success rate with 24-month follow-up.…”
Section: Discussionsupporting
confidence: 90%
“…At our institution, the USLH technique came into more common practice in 2016, utilizing a similar technique to uterosacral ligament colpopexy and as presented previously [26]. The median follow-up time after USLH in the present study was 23 months for the retrospective portion of the study, at which time no patients had undergone retreatment, and is similar to the study by Aserlind et al [16].…”
Section: Discussionsupporting
confidence: 83%
“…Although their reoperation rate was higher than what we reported in our study, their reported subjective recurrence incidence was in line with our findings. Last, Aserlind et al retrospectively reviewed 40 patients who had undergone transvaginal USLH with an average follow-up time of 17.2 months and found significant anatomical improvements with no reoperation for recurrent POP [16]. At our institution, the USLH technique came into more common practice in 2016, utilizing a similar technique to uterosacral ligament colpopexy and as presented previously [26].…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…Although the mean operating time of TULH is relatively longer, it is still encouraging with respect to recurrence outcomes, with an overall failure incidence of 5% at a mean follow-up of 17 months. 26 We believe that the choice between laparoscopic or vaginal surgery depends on the individual's situation and expertise of doctors.…”
Section: Discussionmentioning
confidence: 99%